Analysis Persyaratan Mata Kuliah Bahasa Inggris Pada Jurusan Ekonomi Syariah STES Manna Wa Salwa - Muthia Rahman (Sekolah Tinggi Ekonomi Syariah (STES) Manna wa Salwa, 2022)
Abstrak The purpose of this study is to recognize the analysis of the needs of English for Economics subject at Ekonomi Syariah department. It focuses on analyzing the targets and learning requirement. All of the Ekonomy Syariah students of STES Manna Wa Salwa Tanah Datar Sumatera Barat became the subjects of this research. This study was conducted under qualitative method. The instruments for the study were questionnaire and interview. The data showed that the objective of English for Economics subject at Economi Syariah department was being able to communicate in English actively oral or written that can be implemented for the future field of work. The analysis of learning needs told the result that the learners required the speaking skills properly in order to get them to be able to involve into the real practice of job in the future. The components of good speaking skills that were related to the needs for the future job were very crucial to be accomplished, as a result learners could comuunicate in English fluently and properly. Consequently, the results of the study are expected to be consideration for planning the lesson plan and learning materials. Keywords : Analysis, Learning needs, English for Economics